MODEL SKENARIO PENGGUNAAN LAHAN BERBASIS CELLULAR AUTOMATA-MARKOV CHAIN SEBAGAI SISTEM PENDUKUNG KEPUTUSAN SPASIAL UNTUK PERENCANAAN KOTA SAMARINDA - Kardika, Adelia Juli; Kamarati, Kiamah Fathirizkia Agsa; Faradilla, Faradilla; Ningsih, Rusdiana; Dinata, Nur Rahma Muzaddiyah (Lambung Mangkurat University-Indonesia, 2024)
The city of Samarinda is one of the supporting cities for Indonesia's new capital city. This will of course have an impact on increasing infrastructure development in Samarinda. Land use scenario modeling is an effective alternative that can be used to understand land conditions by analyzing and simulating future land use scenarios. The aim of this research is to create a land use scenario model which can later be used as a spatial decision support system in policy making related to Samarinda city spatial planning and sustainable governance. The method used in this research is a combination of the Cellular Automata (CA)-Markov Chain model with Remote Sensing-GIS. The results of this research show that the Celelu Automata-Markov Chain based land use scenario model shows that in 2034 Samarinda City will experience an increase and decrease in area in several land uses. There has been a significant increase in the area of land use, namely settlements, mining, dry land farming mixed with bushes, and dry land farming. From CA-Markov modeling, changes in LULC will occur in the future. The detailed analysis in this research will be very useful as basic data information to help city planners and local governments for future planning and development as well as technical knowledge about landscape changes.